Optimizing Family Welfare Education Management through Information Technology: A Case Study Approach - Tambingon, Henny; Tangkere, Telly F S (International Journal of Information Technology and Education, 2025)
This study explores the integration of information technology (IT) in optimizing educational management within the Family Welfare Department of a vocational higher education institution. Using a qualitative case study approach, data were collected through semi-structured interviews, direct observations, and document analysis involving department heads, lecturers, administrative staff, and students. Thematic analysis was applied to identify key strategies, supporting factors, challenges, and solutions related to IT adoption. Findings reveal that IT integration improves administrative efficiency, enhances curriculum management, and fosters better communication among stakeholders. Key enablers include leadership commitment, ongoing training, and adequate infrastructure. However, challenges such as limited human resources, resistance to change, and unstable internet connectivity persist. The study recommends a phased implementation strategy, targeted professional development, and policy support to strengthen IT-based management. This research contributes to the understanding of technology-enhanced educational management in vocational settings, offering practical insights for similar departments seeking digital transformation.